Immunoaffinity chromatography and gentle IAC purification of complexes - Burgess, Richard R. (Henry Stewart Talks, 2021)
Protein purification, Immunoaffinity chromatography, Monoclonal antibodies vs. polyclonal antibodies, Fusion protein purification methods